Can Headache Be a Symptom of Celiac Disease?: A University Hospital Experience - Habip Almış; Müsemma Karabel; Fedli Emre Kılıç; Sibel Yavuz; Rojan İpek (Lokman Hekim Dergisi, 2025)
Aim: The purpose of this study was to determine the prevalence of Celiac disease in pediatric patients presenting with headache. However, little is known about the co-morbidity of Celiac disease and headache. To our knowledge, this is the first prospective pediatric study that systematically reviews this topic. Method: Two hundred forty four patients referred to the Pediatric neurology clinic of Adıyaman University Training and Research Hospital between January 2021 and November 2022 were examined. Gender, age, type of headache, Celiac serology, and other laboratory parameters of the cases meeting the inclusion criteria were recorded. Upper gastrointestinal endoscopy was performed on patients with positive Celiac serology. Patients whose results were compatible with Celiac disease were placed on a gluten-free diet. Results: The study group consisted of 202 patients, 123 girls (60.9%). The patients’ mean age was 12.67±3.524 years. Tension-type headache was determined in 121 (59.9%) of the patient group, and migraine type in 81 (40.1%). Celiac disease was detected in 5.4%. Vitamin B12 were 211±79.1 pg/ml, ferritin 19.5±13.9 ng/mL, and vitamin D 17.6±9.86 ng/ml (n=193). Interestingly, all patients who were diagnosed with Celiac disease reported that headache complaints decreased with the diet, However, no statistically significant correlation was found between any laboratory finding and headache type. Conclusion: Although it is still controversial whether headache is common in children with celiac disease, the results of our study showed that neurological symptoms improved after gluten-free diet in children presenting with headache and diagnosed with celiac disease. Celiac disease should be investigated in persistent headache despite pharmacological treatment.